Strategic Planning Distressed Areas In Kerman (Case Study: Neighborhood Khajeh Khezr Kerman) - Mohseni, Amirali; Behrad, Alireza (The Turkish Online Journal of Design Art and Communication, 2016)
The historic Urban of Khaje-KhezrInkerman cannot Serve well to its habitants anymore due to Fatigues of Its structure and also lack of infrastructures. In order to address those problems,This area is losing its population because people which usually live there for long years are leaving there to higher levels areas of city to receive better services but the problem is people which have less annual income are getting replaced by them and it could be the beginning of some new issues such as social and culture fluctuation in that urban which will be increased by time. We cannot find cultural congruity at the named area anymore and vicinity order between the residences is completely vanished due to different types of people there. Movement of pure and main habitants to other areas brought forgetfulness to valuables values, good memories, identity and sense of being belong to this area and when such a things get forget they will cause damage to the building and make them abandoned and just ruined which could be a factor of social harms. In this paper required informations gathered by asking the locals, get visualized by shooting the urban, field view and also providing detailed maps of it and for analyzing the Data SWOT Techniquehas been used.
Keywords: Neighborhood Khajeh Khezr; social and physical stability; sustainability strategies